PENGARUH BRAND IMAGE DAN TRUST TERHADAP MINAT BELI ULANG SKINCARE MS GLOWMELALUI KEPUTUSAN PEMBELIAN AEBAGAI VARIABEL INTERVENING PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MINAT BELI ULANG SALEH SITUBONDO - Hadi, Nihlah Rosanti Citra; Karnadi, Karnadi; Praja, Yudha (Fakultas Ekonomi dan Bisnis, 2022)
Marketing is an important activity carried out by companies in any field, in order to earn a profit in accordance with the company's goals, marketing is a way of producing goods or services for companies so that they can market their products as much as possible. The purpose of this study is to determine how much influence Brand image and Trust have on repurchase intention through purchasing decisions. The data collection technique used is probability sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model Partial Least Square (PLS-SEM).The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Brand image has a significant positive effect on purchasing decisions, Trust has a significantly positive effect on purchasing decisions, Brand image has a significantly positive effect on repurchase intention, Trust has a significant positive effect on repurchase intentions, Decisions Purchasing has a significant positive effect on repurchase intention. The results of the indirect effect hypothesis test indicate that Brand image on repurchase interest through purchase decisions has a significant positive effect, Trust on repurchase interest through purchase decisions has a positive but significant effect.